Topology optimization for simplified structural fire safety. (1st October 2016) - Madsen, Søren; Lange, Nis P.; Giuliani, Luisa; Jomaas, Grunde; Lazarov, Boyan S.; Sigmund, Ole
Highlights: Topology optimization is applied to structural fire safety design. Optimized fire resistant structures differ significantly from standard compliance designs. Detailed sensitivity analysis provides the basis for more complex and realistic fire safety designs. Abstract: Topology optimization is applied in an idealized structural fire safety model, where the minimum compliance problem is constrained by temperature-controlled structural degradation. The constraint ensures a certain structural stiffness after a prescribed time. As this time period is extended, resulting optimized topologies tend to become thicker or introduce redundant members that can take over when structural parts near the origin of the fire lose their load carrying capability. Hence, the structural degradation model acts as an erosion operator on the topology and indirectly enforces a minimum length scale on the final designs.